Effectiveness of Kinesio Video and Pelvik Roxing Exercise Video on Reducing Back Pain of Third Trimester Pregnant Women - Herinawati, Herinawati; Lilis, Dewi Nopiska; Osvinarti, Osvinarti; Novita, Nesi; Iksaruddin, Iksaruddin (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2023)
Background: Back pain in pregnant women is a common problem that is often experienced during pregnancy, especially in the third trimester. Back pain in pregnant women not only interferes with the mother's quality of life, but can also affect fetal well-being and the delivery process. In an effort to address the problem of back pain in pregnant women, various physical therapy methods have been developed. Two methods that have gained attention are Kinesio techniques and Pelvic Roxing Exercises. Method: This research is a quantitative research with a pre-experimental study that uses a one group pretest-posttest design with no control group. The sample of this study was third trimester pregnant women at PMB Latifah and PMB Zainab Jambi City as many as 60 pregnant women. The sampling technique used purposive sampling technique. This research instrument is a questionnaire. Data were analyzed using the mann whitney test. Results: The results showed that in the Kinesia Taping therapy group it was known that before being given Kinesio Taping treatment, the scale of back pain felt by respondents was 67% feeling moderate pain and 33% feeling severe pain controlled. After being given Kinesio Taping, the pain scale felt by respondents was 57% feeling mild pain and 43% feeling moderate pain. In the Pelvic Roxing Exercise therapy group, it is known that before being given Pelvic Roxing Exercise therapy, the scale of back pain felt by respondents is 9% feeling mild pain, 70% moderate pain and 21% severe pain controlled. After being given Pelvic Roxing Exercise therapy, the scale of back pain felt by respondents was 77% mild pain and 235 moderate pain. The results of the mann whitney test obtained p-value = 0.041, p-value <0.05 so that there is a significant difference between the results after kinesio taping and pelvic roxing exercise interventions Conclusion: Based on the results of the study, it can be concluded that there are differences in the scale of back pain in third trimester pregnant women before being given kinesio taping therapy and pelvic roxing exercise with after being given kinesio taping therapy and pelvic roxing exercise.